DAMPAK PEMANENAN KAYU BERDAMPAK RENDAH TERHADAP KERUSAKAN TEGAKAN TINGGAL DI HUTAN ALAM (Studi Kasus di Areal HPH PT. Suka Jaya Makmur, Kalimantan Barat) - Muhdi Muhdi; Diana Sofia Hanafiah (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2007)
The objective of the study was to know the degree of residual stand damages caused by conventional timber harvesting and reduced impact logging in natural forest. The study showed that degree of residual stand damages based on tree population in conventional timber harvesting and reduced impact logging was 33.15% and 19.53% respectively. Based on the size injury of every individual tree, the degree of the trees damages caused by timber harvesting in conventional timber harvesting and reduced impact logging is as follow : trees heavy injury was 64.66% and 57.20%, trees medium injury was 20.30% and 24.00% and trees light injury was 15.03% and 18.80% respectively. These research results indicate that conventional timber harvesting in the tropical natural forest caused heavier damage on residual stand when compared with a reduced impact logging.